Pemanfaatan Media Audio Visual dan Media Gambar Pada Siswa Kelas V - Hery Setiyawan (Jurnal Prakarsa Paedagogia, 2021)
This research was conducted with the aim of knowing the average test result score as a reflection of the effectiveness of audio visual media and image media. This is based on learning outcomes that are considered less than optimal and many are still incomplete because teachers are accustomed to the use of image media in learning. The selection of audio-visual media as a way of teaching data presentation material is because it has better features than just ordinary images. This study determined the subject, namely the fifth grade students at one of the private elementary schools in Surabaya which had 34 students. The results of this study presented an average of learning outcomes in a class using audio visual media was 87.68. In another class, the average result of student learning in the class using image media obtained an average result of 79.59. The conclusion from these results is that the class that uses audio-visual media is more effective than the class that uses image media.